Statistical effects of waterway lock unavailability on commodity flow. Issue 6 (2nd November 2019) - Chimka, Justin R.; Fernandez De Luis, Adrian; McGee, Grace W.
ABSTRACT: Problem statemen t : It has been posited that insufficient funding for lock maintenance on the inland waterway system causes scheduled and unscheduled delays that greatly threaten inland waterway system performance. We seek to express this in a concrete form and explore quantitatively the extent to which it may be true. Approach : Our approach is to estimate statistical models using Lock Use, Performance, and Characteristics data published by the US Army Corps of Engineers (USACE) Navigation Data Center. Important to this approach are that the models should seem practically appropriate, and special attention should be paid to the possibility of interaction among lock unavailability and usage variables. Results : Apparently, the cost of scheduled unavailability for lock maintenance expressed in disrupted commodity flow is in its fixed component; the decision to interrupt commodity flow is what affects inland waterway system performance compared with the extent to which flow is interrupted in time. At the same time, the cost of unscheduled unavailability (e.g. lock closures due to disrepair and natural causes) is in its variable component, meaning the extent to which flow is interrupted in time more greatly affects inland waterway system performance.